T cells recognizing a peptide contaminant undetectable by mass spectrometry. - Vedran Brezar (Public Library of Science (PLoS), 2011)
Synthetic peptides are widely used in immunological research as epitopes to stimulate their cognate T cells. These preparations are never completely pure, but trace contaminants are commonly revealed by mass spectrometry quality controls. In an effort to characterize novel major histocompatibility complex (MHC) Class I-restricted β-cell epitopes in non-obese diabetic (NOD) mice, we identified islet-infiltrating CD8+ T cells recognizing a contaminating peptide. The amount of this contaminant was so small to be undetectable by direct mass spectrometry. Only after concentration by liquid chromatography, we observed a mass peak corresponding to an immunodominant islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP)(206-214) epitope described in the literature. Generation of CD8+ T-cell clones recognizing IGRP(206-214) using a novel method confirmed the identity of the contaminant, further underlining the immunodominance of IGRP(206-214). If left undetected, minute impurities in synthetic peptide preparations may thus give spurious results.